Application of the Constructed Wetland Method in Efforts to Manage Acid Mine Water Waste in Coal Mining, Based on Literature Review - Wina, Andrawina; Rika Ernawati; Tedy Agung Cahyadi; Waterman SB; Nur Ali Amri (ReTII, 2020)
An important problem that often occurs due to open pit mining activities from coal mining is the problem of acid mine drainage. Acid mine drainage is formed due to the oxidation of sulfide minerals that are exposed to the outside and then mixes with water, resulting in acidic water and also acid mining water often contains suspended solids that have high concentrations. This acidic mining waste can cause corrosion and dissolve metals so that contaminated water is toxic and can destroy aquatic life. Handling of acid mine drainage as passive treatment with constructed wetland methods is often applied to acid mine drainage treatment in several coal mining companies. By applying the method of constructed wetlands in the handling of acid mine drainage, it is effective in increasing the pH value and reducing the dissolved heavy metal content. This research is to find a management method for acid mine drainage using the constructed wetland method, so it is reviewed again to assist the management process of acid mine drainage by passive treatment with the constructed wetland method. The review was conducted to compare the management method of acid mine drainage with the constructed wetland method and to find out the advantages and disadvantages of swamp plants used in the artificial wetland method.